The Reality Use of Printed Learning Resources and its Role in Serving the Scientific Research from the view point of the Postgraduate Students-A field study at Tishreen University- - Ali, Kheder; Ireeq , Najla (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The present study aims to find out the reality of postgraduate students’ use of printed learning resources and its role in serving the scientific research. The sample of the study is all postgraduate students enrolled in Tishreen University colleges. The researcher has relied on the descriptive approach and used the questionnaire as a research tool in order to find out the reality of postgraduate students’ use of printed learning resources and its role in serving the scientific research. The study has found that the most important printed sources used by the postgraduate students at Tishreen University are printed books, followed by periodicals. Moreover, there were statistically significant differences at (0.05) among the answers of the research sample members, Tishreen postgraduate students, concerning the services provided by the libraries of the scientific research, especially the printed sources, and regarding the difficulties of using the libraries in the scientific research, especially the printed sources, according to the variable of College Type. However, there were no statistically significant differences among the answers of the research sample members regarding the previous two topics according to the variable of the Academic Year.